Sistem Informasi Inventaris dan Pengemasan Aksesoris Mebel di PT. Fittech Anugrah Mekarindo Perkasa - Mulky Fadillah, Muhamad; Primasari, Dewi; Kamilah, Nurul (Jurnal Etnik: Ekonomi-Teknik, 2023)
Inventory or inventory is the storage of raw materials, materials or finished goods for use in the future or at a certain time. Packaging can be interpreted as the act of wrapping, covering an item or a group of items with packaging material. PT.Fittech Anugrah Mekarindo Perkasa is a company that focuses on providing high quality furniture and various accessories to meet market demand in the production of furniture/furniture, the current problems are (1) the occurrence of differences in goods between accessories stock data and actual accessories stock when stock taking is carried out, (2) accessories stock data is often lost due to the negligence of the warehouse operator when preparing the goods, (3) the packaging operator takes new accessories for production shortages without providing information to the warehouse operator. Based on these problems, it is hoped that with the research entitled "Inventory Information System and Packaging of Furniture Accessories at PT. Fittech Anugrah Mekarindo Perkasa”, makes it easier to control the availability of accessories, increases accuracy when managing accessories stock data so that it can produce accurate accessories stock data information. Then for the system development method that will be used is the waterfall method, with the stages of system development starting from analysis, design, coding and testing.